Analysis of Solar Power Plant Implementation as Renewable Energy in Learning at Wisuda Karya Vocational High School, Kudus - F. Shoufika Hilyana; Margareta Rahayuningsih; Aditya Marianti (Universitas Negeri Semarang, 2024)
This article examines the implementation of Solar Power Plants (Id. Pembangkit Listrik Tenaga Surya - PLTS) as renewable energy sources in the learning process at Wisuda Karya Vocational High School, Kudus. The utilization of renewable energy, particularly solar power, has gained significant attention due to its sustainability and environmental benefits. The study aims to analyze the effectiveness and challenges of integrating PLTS into the curriculum at the vocational high school level. Through qualitative research methods, including interviews and observations, data were collected to assess the impact of PLTS implementation on students' learning experiences and environmental awareness. The findings indicate positive outcomes in terms of student engagement, practical knowledge acquisition, and environmental consciousness. However, several challenges were identified, such as initial investment costs, technical maintenance, and curriculum integration. Recommendations for addressing these challenges and optimizing PLTS implementation in vocational high school education are provided. This article contributes to the discourse on renewable energy education and offers insights for educators and policymakers interested in promoting sustainable practices in vocational learning environments.